Economic Inclusion Program Cohort 2 in Kenya: Baseline Household Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset consists of household-level data collected through a baseline survey conducted between April and May 2024 for the Impact Evaluation of the Economic Inclusion Programme (EIP), Cohort 2, in Kenya. The survey covers 3,251 households across four counties, Kisumu, Makueni, Muranga, and Taita Taveta, and was implemented by the Kenyan survey firm REMIT.